Contextual Effect of Place 0f Birth Delivery on Depression in Karanganyar, Central Java - Jannah, Ahadyah Miftahul; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2019)
Background: Postpartum depression is a common mental health problem that usually occurs in women after childbirth. According to WHO, there are 377 million people in depression worldwide. In Indonesia, the prevalence of depression sufferers is 3.7%, and those who experience anxiety are 3.3%. Postpartum depression that is not immediately treated can cause an impact in nursing, namely communication and response is reduced, the existence of negative interactions, the existence of hostility, the existence of impaired competence. This study aimed to analyze the determinants of postpartum depression at the individual level and the contextual effect of place of birth delivery. Subjects and Method: This was a cross sectional study conducted in Karanganyar, Central Java, from November to December 2018. A sample of 200 postpartum mothers was selected by random sampling. The dependent variable was postpartum depression. The independent variables were stress level, work, income, education, pregnancy status, parity, coping strategy, and labor compli